1978
DOI: 10.1139/g78-062
|View full text |Cite
|
Sign up to set email alerts
|

Dna Content, Ribosomal-Rna Gene Number, and Protein Content in Soybeans

Abstract: Six cultivars and five plant introductions of Glycine rnax L. Merr. varied in picograms of DNA per cell from B .$4 to 2.61, and in number of ribosomal-RNA genes per 2 C nucleus from 968 to 243 1 (Laboratory 1, Ames) and from 768 to 2095 (Laboratory 2, Rhinelander). The parameters did not correlate with seed protein content, which varied from 32.8% to 52.6%. With these materials, use of the rRNA locus size as a breeding tool for increasing percentage protein content by use of cytogenetic and genetic manipulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The data for cotyledons are for single cotyledons or portions of a single cotyledon. Haploid nuclear genome size given for Arabidopsis thaliana is from [12] and for Glycine max is from [7]. The value given for Citrullus vulgaris represents the mean of the range of 0.7-1.5 pg for seven cucurbit species [ 10].…”
Section: Resultsmentioning
confidence: 99%
“…The data for cotyledons are for single cotyledons or portions of a single cotyledon. Haploid nuclear genome size given for Arabidopsis thaliana is from [12] and for Glycine max is from [7]. The value given for Citrullus vulgaris represents the mean of the range of 0.7-1.5 pg for seven cucurbit species [ 10].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have suggested that nuclear DNA content variation exists in soybean lines. Doerschug, Mikche, and Palmer (1978) evaluated 11 soybean cultivars and found that the DNA amount varied between 1.84 pg and 2.62 pg per 2C nucleus (Doerschug et al, 1978). Graham, Nichell, and Rayburn (1994) examined 20 soybean cultivars and observed a 15% variation in genome size (Doerschug et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the actual extent and the functional significance of DNA content variation within a species still appear rather obscure. Some questions may be posed: i) GREENLEE et al 1984CAVALUNI et al 1986PRICE et al 1981aPRicE et al 1980DoERSCHUG et al 1978YAMAMOTO and NAGATO 1984CAVALLINI and NATALI 1990RAINA and REEs 1983AINswoRTH et al 1983KENTON 1984JoNES and KENTON 1984FuRUTA 1970FURUTA and NISHIKAWA 1977FURUTA and NISHIKAWA 1977GRIME 1983NAGATO et al 1981NAGATO et al 1981BENNETT et al 1977CARROZZA et al 1980RAYBURN et al 1985 how many cases of nuclear DNA variation are known and well-documented? ii) what DNA sequences are involved in the variations?…”
Section: Introductionmentioning
confidence: 99%